Barrels XXIX: Barrels go Hollywood. (2nd January 2017) - Evans, Mathew H.; Brumberg, Joshua C.
Abstract: Barrels XXIX brought together researchers focusing on the rodent barrel cortex and associated systems. The meeting revolved around three themes: thalamocortical interactions in motor control, touch in rodent, monkey, and humans, and the nature of the multisensory computations the brain makes. Over two days these topics were covered as well as many more presentations that focused on the physiology, behavior, and development of the rodent whisker-to-barrel cortex system.